Preterm birth leads to a decreased number of differentiated podocytes and accelerated podocyte differentiation - Zhang, Lulu; Chen, Zhihui; Gao, Qi; Liu, Ge; Zheng, Jun; Ding, Fangrui (Frontiers in Cell and Developmental Biology, 2023)
Preterm birth was previously identified as a high-risk factor for the long-term development of chronic kidney disease. However, the detailed pattern of podocyte (PD) changes caused by preterm birth and the potential mechanism underlying this process have not been well clarified. In present study, a rat model of preterm birth was established by delivery of pups 2 days early and podometric methods were applied to identify the changes in PDs number caused by preterm birth. In addition, single-cell RNA sequencing (scRNA-seq) and subsequent bioinformatic analysis were performed in the preterm rat kidney to explore the possible mechanism caused by preterm birth. As results, when the kidney completely finished nephrogenesis at the age of 3 weeks, a reduction in the total number of differentiated PDs in kidney sections was detected. In addition, 20 distinct clusters and 12 different cell types were identified after scRNA-seq in preterm rats (postnatal day 2) and full-term rats (postnatal day 0). The numbers of PDs and most types of inherent kidney cells were decreased in the preterm birth model. In addition, 177 genes were upregulated while 82 genes were downregulated in the PDs of full-term rats compared with those of preterm rats. Further functional GO analysis revealed that ribosome-related genes were enriched in PDs from full-term rats, and kidney development-related genes were enriched in PDs from preterm rats. Moreover, known PD-specific and PD precursor genes were highly expressed in PDs from preterm rats, and pseudotemporal analysis showed that PDs were present earlier in preterm rats than in full-term rats. In conclusion, the present study showed that preterm birth could cause a reduction in the number of differentiated PDs and accelerate the differentiation of PDs.